2016
DOI: 10.1080/08820538.2016.1177098
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Macular Ganglion Cell Complex Thickness and Central Macular Thickness after Argon Laser Panretinal Photocoagulation

Abstract: GCC thickness increased significantly until month 6 compared with baseline values in most of the macular segments post-PRP in the PDR group. The GCC thickness at month 12 was not different from the baseline thickness in any of the macular segments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Over the long-term followup, they gradually returned to the baseline level. Many of the previous studies using OCT obtained similar results (27,28). They considered that the retinal inflammation and edema caused by PRP at the early postoperative phase could damage the retinal neural cell and tissue and later recovery might be attributed to the absorption and healing of the edema and the laser-induced photoreceptors and ganglion cell damage.…”
Section: Discussionmentioning
confidence: 72%
“…Over the long-term followup, they gradually returned to the baseline level. Many of the previous studies using OCT obtained similar results (27,28). They considered that the retinal inflammation and edema caused by PRP at the early postoperative phase could damage the retinal neural cell and tissue and later recovery might be attributed to the absorption and healing of the edema and the laser-induced photoreceptors and ganglion cell damage.…”
Section: Discussionmentioning
confidence: 72%
“…In argon laser photocoagulation, the laser energy is absorbed by the retinal pigment epithelium (RPE) and generates thermal energy to the outer retina. Heat damage in the inner retinal layers causes edema due to increased vascular permeability and presents as increased retinal thickness 20 . As expected, the authors observed a mild increase in macular thickness during the 12 months post PRP.…”
Section: Discussionmentioning
confidence: 99%
“…The macular region retinal nerve fiber layer was reported to increase in the short-term [15] due to axonal edema but decrease thereafter since standard PRP with Argon laser [16]. The increased vascular permeability in the superficial vascular plexus associated to heat damage was reported to increase the thickness of the macular ganglion cell complex in the initial months, with subsequent return to baseline values at 12 months in one study [17] but not in another one [18]. According to the authors' knowledge, this is the first study reporting measurements on these retinal layers on a long-term basis.…”
Section: Discussionmentioning
confidence: 97%